Nasopharyngeal sarcoidosis: case reports and literature review - Benettini, Giacomo; Bruschini, Luca; Fiacchini, Giacomo; Vianini, Matteo; De Santi, Silvia; Sparacino, Lucrezia; Donati, Valentina; Berrettini, Stefano; De Vito, Andrea (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis is a multisystemic inflammatory chronic disease characterized by the presence of noncaseating granulomas most frequently in lungs and in intrathoracic lymph nodes. The nasopharyngeal form is unusual and noncommon in the ENT practice. Background and objectives: In order to establish a correct knowledge about this rare disease, we report two different cases of nasopharyngeal sarcoidosis moreover all the available literature is reviewed. Materials and Methods: A systematic literature review was made through PubMed databases, according to the PRISMA guidelines [1], combining the following key words: Nasopharyngeal, Rhinopharynx, Sarcoidosis, in publications between 1951 and 2020. Results: 16 articles reported 27 cases of nasopharyngeal sarcoidosis. The number of males was 13 (48,2%) and the number of females was 14 (51,8%) with a mean age at the diagnosis of 35,28 ± 13.05 years old (range 5 - 64). In 16 (59,3%) cases nasopharyngeal sarcoidosis was associated with lungs and/or intrathoracic lymph nodes involvement; nasal obstruction was the most frequently reported symptom (51,8% of subjects). Conclusions:Nasopharyngeal sarcoidosis can mimic several disorders of the upper airway respiratory tract and it must therefore be considered in the differential diagnosis. A biopsy of nonspecific lesions in the nasopharynx is always advisable because it can allow an early diagnosis of sarcoidosis.